2020
DOI: 10.3390/cryst10111004
|View full text |Cite
|
Sign up to set email alerts
|

New Coordination Compounds of CuII with Schiff Base Ligands—Crystal Structure, Thermal, and Spectral Investigations

Abstract: The new mono-, di- and tetranuclear coordination compounds [Cu(HL1)]·H2O (1), [Cu2(L1)(OAc)(MeOH)]·2H2O·MeOH (2), [Cu4(L2)2(OAc)2]·4MeOH (3), and [Cu4(L2)2(OAc)2]·4H2O·4MeOH (4) were synthesized by the direct reaction of 2,2′-{(2-hydroxypropane-1,3-diyl)bis[nitrilomethylidene]}bis(4-bromo-6-methoxyphenol) (H3L1) or 2,2′-{(2-hydroxypropane-1,3-diyl)bis(nitriloeth-1-yl-1-ylidene)}diphenol (H3L2) and the Cu(II) salt. They were characterized by elemental analysis, X-ray fluorescence (XRF), Fourier transform infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…The Cu(1) and Cu(2) centers have slightly distorted square pyramidal coordination geometries (Figures 5 and S3) in which the equatorial sites are occupied by two nitrogen and two oxygen atoms of Schiff base ligands. The Cu-O and Cu-N bonds are within normal values (C-O 1.913(4)-1.983(5) Å and C-N 1.960(5)-1.977(5) Å) and comparable to those observed in the related Cu II compounds [40,43,[46][47][48][49]. The apical positions are occupied by oxygen atoms from monodentate nitrate ions and the bond lengths are found to be significantly longer (distances in the range 2.410(6)-2.649(5) Å) than those of Cu-O in the basal plane.…”
Section: Crystal and Molecular Structuresupporting
confidence: 72%
See 1 more Smart Citation
“…The Cu(1) and Cu(2) centers have slightly distorted square pyramidal coordination geometries (Figures 5 and S3) in which the equatorial sites are occupied by two nitrogen and two oxygen atoms of Schiff base ligands. The Cu-O and Cu-N bonds are within normal values (C-O 1.913(4)-1.983(5) Å and C-N 1.960(5)-1.977(5) Å) and comparable to those observed in the related Cu II compounds [40,43,[46][47][48][49]. The apical positions are occupied by oxygen atoms from monodentate nitrate ions and the bond lengths are found to be significantly longer (distances in the range 2.410(6)-2.649(5) Å) than those of Cu-O in the basal plane.…”
Section: Crystal and Molecular Structuresupporting
confidence: 72%
“…The involvement of the phenolic oxygen atoms in the metal-ligand bonding is confirmed by the strong doublet bands observed at 1251 cm −1 , 1218 cm −1 1 and 1248 cm −1 , 1219 cm −1 2, respectively. The typical absorption band of the ν aryl -O vibration is identified in the free ligand spectrum at 1233 cm −1 [4,13,[38][39][40][41][42][43][44]. All these spectroscopic features are confirmed by the X-ray structures.…”
Section: Infrared Spectramentioning
confidence: 55%
“…However, the coordination modes as well as hapticity of the ligands in this complex are different from each other. Here it should be noted that the possible coordination modes of symmetrical N 2 O 3 ligand derive from condensation of 1,3‐diamino‐2‐propanol with o ‐hydroxyacetophenone or its derivatives are reported by Bartyzel et al [5j] . Coordination features of the ligands in this complex are depicted in Scheme 2.…”
Section: Resultsmentioning
confidence: 60%
“…These compounds have been extensively investigated due to their physical-chemical properties, such as thermochromism and photochromism, role played in catalytic biochemical processes, coordination chemistry, organic synthesis, technological applications, and design of anticancer drugs. [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] Some o-Hydroxy aryl schiff bases present a keto-enol tautomeric equilibrium [see Figure 1] which is a consequence of a proton transfer process in the intramolecular HB that gives rise to two tautomeric forms, enol-imine (or OH-) and ketoamine (or NH-). [65][66][67][68] Spectroscopic data obtained by applying different techniques such as heteronuclear NMR in both phases, FT-IR spectroscopy, X-ray and neutron diffraction, have shown that OH form predominates in solution, with a few exceptions, while in the solid state the tautomeric equilibrium is strongly shifted towards to the NH form.…”
Section: A Very Interesting Class Of Compounds Containing Strong Intr...mentioning
confidence: 99%